2010
DOI: 10.3892/or.2010.941
|View full text |Cite
|
Sign up to set email alerts
|

The antitumor and antimetastatic effects of N-trimethyl chitosan-encapsulated camptothecin on ovarian cancer with minimal side effects

Abstract: Abstract. Lymphatic metastasis plays a critical role in ovarian cancer, indicates poor prognoses and correlates to the majority of cancer deaths. Camptothecin derivatives exhibit promising activity for the treatment of solid tumors because of its specific inhibition of eukaryotic DNA topoisomerase I. Yet, its application is hindered due to extreme water insolubility and severe side effects. It is essential to establish an efficient and safe protocol for the administration of camptothecin versus tumor metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The nude mice were randomly assigned to three groups (six mice/group). WT-SK, EV-SK, VEGFD-SK cells were injected subcutaneously with 2×10 6 cells into the left hind paws of mice respectively ( 25 ). The tumor volume was determined by the following formula: tumor volume (mm 3 ) = 0.52 × length (mm) × width (mm) × height (mm).…”
Section: Methodsmentioning
confidence: 99%
“…The nude mice were randomly assigned to three groups (six mice/group). WT-SK, EV-SK, VEGFD-SK cells were injected subcutaneously with 2×10 6 cells into the left hind paws of mice respectively ( 25 ). The tumor volume was determined by the following formula: tumor volume (mm 3 ) = 0.52 × length (mm) × width (mm) × height (mm).…”
Section: Methodsmentioning
confidence: 99%
“…From the studies reviewed it is concluded that Chitosan and Chitosan derivatives are promising polymeric excipients for mucosal drug and vaccine derivatives [65,66,68,69,71]. This absorption enhancing effect of Chitosan is caused by opening of the intercellular tight junctions, thereby favouring the paracellular transport of macromolecular drugs.…”
Section: Chitosan and Its Derivatives In Mucosal Drug And Vaccine Delmentioning
confidence: 99%
“…As a traditional herbal medicine, CPP’s cardiotonic and diuretic activity have been well recognized [28]. Recent studies have shown that CPP can inhibit the proliferation and promote the apoptosis in several cancer cells [2931]. Previously we have shown that CPP has the anti-tumor activity in gastric cancer and colon cancer [29, 31], partly through inhibition of the Wnt/β-catenin pathway [29, 32].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that CPP can inhibit the proliferation and promote the apoptosis in several cancer cells [2931]. Previously we have shown that CPP has the anti-tumor activity in gastric cancer and colon cancer [29, 31], partly through inhibition of the Wnt/β-catenin pathway [29, 32]. In other studies, CPP was found to induce the expression of DRs and enhance TRAIL-induced apoptosis in hepatocellular carcinoma cells that were resistant to TRAIL, while the mechanism of which is still unclear until now [33].…”
Section: Introductionmentioning
confidence: 99%